2014
DOI: 10.3322/caac.21212
|View full text |Cite
|
Sign up to set email alerts
|

Cancer screening in the United States, 2014: A review of current American Cancer Society guidelines and current issues in cancer screening

Abstract: Answer questions and earn CME/CNE Each year the American Cancer Society publishes a summary of its guidelines for early cancer detection, a report on data and trends in cancer screening rates, and select issues related to cancer screening. In this issue of the journal, we summarize current American Cancer Society cancer screening guidelines. In addition, the latest data on the use of cancer screening from the National Health Interview Survey is described, as are several issues related to screening coverage und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
166
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 110 publications
(211 reference statements)
0
166
1
3
Order By: Relevance
“…The nature of prostate cancer is such that as long as there is no local progression or metastasis to other parts of the body, it usually does not cause any symptoms (10), and on presentation of symptoms, the disease usually has run its course. Therefore, early detection of the disease in its early stages can be an effective measure in reducing its mortality rate in asymptomatic men (11,12), and creates an opportunity to use effective and inexpensive treatment methods (13). The detection phase is an important factor in the expression of the cancer-related survival rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of prostate cancer is such that as long as there is no local progression or metastasis to other parts of the body, it usually does not cause any symptoms (10), and on presentation of symptoms, the disease usually has run its course. Therefore, early detection of the disease in its early stages can be an effective measure in reducing its mortality rate in asymptomatic men (11,12), and creates an opportunity to use effective and inexpensive treatment methods (13). The detection phase is an important factor in the expression of the cancer-related survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…The five-year survival rate in men with localized (i.e., without metastasis) prostate cancer is almost 100%, while the rate among men with prostate cancer that has metastasized to other parts of the body is only 31% (11). certainly lead to increased diagnosis in the early stages, and therefore to treatment (12). The effectiveness of prostate cancer screening methods to identify the disease and reduce mortality from it has been proven, as various studies have shown reduced mortality from prostate cancer through screening programs (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer is the most common type of cancer diagnosed in men, which would seem to support the benefit of screening [5]. However, prostate cancer is often indolent, and the majority of men older than 85 years have prostate cancer on autopsy [6].…”
Section: Controversies In Prostate Cancer Screeningmentioning
confidence: 99%
“…The ACS now recommends that health care providers inform men 50 years of age or older about the pros and cons of PSA screening so that patients can make an informed decision [5]. As additional years of follow-up accrue from the aforementioned trials, evidence regarding the benefits and harms of PSA screening may evolve, and recommendations may be changed.…”
Section: Controversies In Prostate Cancer Screeningmentioning
confidence: 99%